Efektifitas Pendidikan Kesehatan Media Audio Visual (Video) Dan Demonstrasi Terhadap Ketrampilan Praktik Sadari - Sri Hartutik; Alfrista Dian Pradani - STIKES ‘Aisyiyah Surakarta (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2020)
Abstract: Breast cancer is a cancer with the highest percentage of new cases that amounted to 43.3% and the percentage of deaths due to breast by 12.9%. Based on data obtained from the Surakarta City Health Office breast cancer patients in the city of Surakarta about 9,320 people. Breast self-examination is one of the breast cancer prevention. Health education has various media and method one of them is by method of demonstration and video media. This research is to Knowing the effectiveness of health education with audio visual method (Video) and demonstration to the ability of breast self-examination practice (SADARI) on student SMK Batik 2 Surakarta.This research using methode Quasy Experiment Design research with Pre-Post Test With Control Group design. The subject is 60 female students in SMK Batik 2 Surakarta. The result of bivariate test using Wilcoxon test proves that there is significant influence of the ability of breast self-examination practice after being given demonstration method with Pvalue; 0.000 <0.05 and proved to have a significant effect on the ability of breast self-examination practice after being given video with Pvalue; 0,000 <0.05. While Mann Whitney U test proves there is a difference in the effectiveness of the ability of own breast self-examination practices on students after vocational education was given a demonstration and video health with value Pvalue; 0.001 <0.005. There is influence of health education effectiveness by demonstration method and audio visual media (video) to SADARI practice skill in SMK Batik 2 SurakartaKeywords: Health Education,Video,Demonstration,Breast self examination practice Abstrak: Kanker payudara merupakan penyakit kanker dengan persentase kasus baru tertinggi sebesar 43,3 % Berdasarkan data dari Dinas Kesehatan Kota Surakarta penderita kanker payudara di Kota Surakarta sekitar 9.320 orang. Pendidikan kesehatan mempunyai berbagai media dan metode salah satunya ialah dengan metode demonstrasi dan media video. Penelitian ini untuk Mengetahui efektivitas pendidikan kesehatan dengan metode audio visual (Video) dan demonstrasi terhadap kemampuan praktek SADARI pada siswi SMK Batik 2 Surakarta. Penelitian ini dengan metode Quasy Eksperiment Design dengan rancangan Pre-Post Test With Control Group. Subjeknya yaitu 60 siswi di SMK Batik 2 Surakarta. Hasil uji bivariat menggunakan uji Wilcoxon ada pengaruh kemampuan praktik pemeriksaan payudara sendiri setelah diberikan metode demonstrasi dengan Pvalue;0,000<0,05 dan ada pengaruh signifikan kemampuan praktik pemeriksaan payudara sendiri setelah diberikan video dengan Pvalue;0,001<0,05. Uji Mann Whitney U test ada perbedaan efektifitas kemampuan praktik pemeriksaan payudara sendiri yang signifikan pada siswi SMK sesudah diberi pendidikan kesehatan demonstrasi dan video dengan nilai Pvalue;0,003<0,05. Ada pengaruh efektifitas pendidikan kesehatan dengan metode demonstrasi dan media audio visual (video) terhadap ketrampilan praktik SADARI di SMK Batik 2 SurakartaKata Kunci : Pendidikan Kesehatan,Video,Demonstrasi,Sadari